Designing assessment for inclusion: How does culture fit in? - Joanna Hong-Meng Tai (Muslim Education Review, 2025)
Inclusion is important in higher education, and therefore should be an important consideration within assessment. Over time, the focus of who should be included in higher education has evolved, starting with disability inclusion, and broadening to various aspects of social inclusion. In the context of increasingly internationalized higher education, one contemporary consideration is that of culture. However, what culture is and how it might be accounted for within assessment has not been the focus of prominent scholarly work. This paper undertakes a scoping literature review to establish what is already known, and to offer directions for future work. Through the review, two design principles are developed which speak to the broader movement towards assessment for inclusion. Though culture is ill-defined within the literature, this may be more important to consider within local contexts rather than at a conceptual level. Future research could profitably focus on generating empirical evidence regarding the outcomes of assessment designs which are culturally inclusive, and exploring the implications of implementation for educators and institutions.